L’« autre » l’étranger dans « l’Hôte » d’Albert Camus - Fernando Gomes (Carnets)
Camus was basically ignorant to what concerns the Arabic language and culture, which has confined its perception of the alterity. Accused of being a colonialist and even a racist by some postcolonial theorists, Camus, it is true, shows some distortion of History in his literary work, specifically with regard to colonial responsibility concerning the extreme poverty of the native population. « L’Hôte » is the most direct and most subtle literary testimony of his position towards the problems of colonial Algeria and his relationship with the « other ». In the exegesis of this short story, we examine the signs revealing the duality of feelings of the protagonist in his interaction with alterity, namely, how his behavior reveals pulses alternately ethical and colonialists. Besides, we unveil the author's pessimism regarding the relations with the « other », the foreigner, mainly in times of conflict.